Holocaust survival in Antwerp : on foreign soil - Kleiman, Alter (Lexington Books, 2023)
"The informal cooperation and collaboration of Christians with the Jewish underground emerges as a key element in this new translation of Alter Kleiman's memoir Holocaust Survival in Antwerp: On Foreign Soil"--